2023
DOI: 10.1126/science.adg8392
|View full text |Cite
|
Sign up to set email alerts
|

Screening strategy for developing thermoelectric interface materials

Liangjun Xie,
Li Yin,
Yuan Yu
et al.

Abstract: Thermoelectric interface materials (TEiMs) are essential to the development of thermoelectric generators. Common TEiMs use pure metals or binary alloys but have performance stability issues. Conventional selection of TEiMs generally relies on trial-and-error experimentation. We developed a TEiM screening strategy that is based on phase diagram predictions by density functional theory calculations. By combining the phase diagram with electrical resistivity and melting points of potential reaction products, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 79 publications
0
20
2
Order By: Relevance
“…As depicted in Figure d, our all-SnTe-based thermoelectric device achieved a maximum power generation efficiency of ∼2.7% at a Δ T of 350 K, demonstrating an important breakthrough for promoting the fabrication and application of environmentally friendly all-SnTe-based devices. However, it is worth noting that there is still significant room for improvement in the power generation performance of the all-SnTe-based thermoelectric devices, which still requires extensive efforts on not only developing high-performance n-type SnTe comparable to that of p-type samples but also investigating more on the interfacial structure and geometry design on the device level …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As depicted in Figure d, our all-SnTe-based thermoelectric device achieved a maximum power generation efficiency of ∼2.7% at a Δ T of 350 K, demonstrating an important breakthrough for promoting the fabrication and application of environmentally friendly all-SnTe-based devices. However, it is worth noting that there is still significant room for improvement in the power generation performance of the all-SnTe-based thermoelectric devices, which still requires extensive efforts on not only developing high-performance n-type SnTe comparable to that of p-type samples but also investigating more on the interfacial structure and geometry design on the device level …”
Section: Resultsmentioning
confidence: 99%
“…However, it is worth noting that there is still significant room for improvement in the power generation performance of the all-SnTe-based thermoelectric devices, which still requires extensive efforts on not only developing high-performance n-type SnTe comparable to that of p-type samples but also investigating more on the interfacial structure and geometry design on the device level. 56…”
Section: Thermoelectricmentioning
confidence: 99%
“…3 In addition, excellent mechanical properties are also crucial for practical applications of thermoelectric devices. 4 This is because thermoelectric devices often suffer complex thermomechanical coupling environments and therefore thermal stress inside the interface between thermoelectric material and barrier layer matters, 5,6 which requires thermoelectric material itself to have good mechanical properties. However, Bi 2 Te 3based thermoelectric materials, which are currently used widely in major commercial applications, have the disadvantages of poor mechanical properties, rooted in the weak van der Waals interaction between two quintuple layers, 7 which limits their application in complex working conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 However, p-type MgAgSbbased TE devices have seen fewer advancements. 34,35 MgAgSb received intensive attention since 2012. 36,37 Subsequently, Zhao et al, 38 Liu et al, 39 Ying et al, 40 Shuai et al, 41 and Zheng et al 42 reported high ZT and PF with good mechanical properties from RT to 300 1C.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the internal resistance of MgAgSb-based devices has increased during the service process, 35,46 suggesting that Ag may not be the optimal solution. 35 Recently, researchers also put lots of effort in the paired MgAgSb-Mg 3 Sb 2Àx Bi x TE device for near room temperature cooling 28,29,46 and power generation. 18,28,34,35,45,46 For example, Xie et al 35 developed a novel engineering roadmap, thereby obtaining MgCuSb TEiMs and then efficiently achieving a high Z of 9.25% under a 300 1C temperature gradient.…”
Section: Introductionmentioning
confidence: 99%